Methylation of 45S Ribosomal DNA (rDNA) Is Associated with Cancer and Aging in Humans - Fengqing Shao; Xiaoqi Liu; Xianzhi Zhang; Qi Wang; Wencai Wang (International Journal of Genomics)
Cancer and aging, two distinct processes of cell development, are two major problems threatening our human health and life in current days. Epigenetic studies, especially DNA methylation, have been intensively investigated on them over the years, though a lot of unanswered issues remain. In the human genome, rDNA is a highly conserved tandem repeat family playing critical roles in protein synthesis, genome stability and integrity, etc. More importantly, rDNA is the significant target of DNA methylation, and a potential association between rDNA methylation and cancer and aging has emerged recently. However, whether there is a general trend that rDNA methylation is associated with cancer and aging remains an open issue. In this study, the involvement of rDNA methylation in a series of records of cancer and aging was investigated and summarized, upon which perspectives about rDNA methylation in cancer and aging were proposed. The results showed that rDNA methylation in most cancer cases displayed a consistent pattern with hypermethylation in the coding region but with hypomethylation in the promoter region, which likely facilitates the proliferation and metastasis of cancerous cells. Distinctively, both the coding and promoter regions of rDNA become increasingly methylated during the process of aging, indicating the decline of rDNA activity. The finding of rDNA methylation also implies its potential application as an epigenetic biomarker in the diagnosis of cancer and aging. This work will shed light on our understanding of the pathogenesis, diagnosis, and treatment of cancer and aging from the perspective of rDNA methylation.